2004
DOI: 10.1177/1524839904264632
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Post-Settlement Influences on State Tobacco Control Funding

Abstract: State settlements with the tobacco industry increased the availability of funds that might be used for improving health outcomes and increased scrutiny of tobacco control funding overall. This research identified potential explanatory factors for state tobacco control funding and developed a conceptual framework to guide further exploration. Key informant interviews with 14 tobacco policy professionals were conducted to augment the information available in the scientific literature on funding influences. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…Interviews and validation focus groups guided by the use of a semistructured guide to assure that the same concepts were explored but allowing a free flowing exploration (Corbin & Strauss, 2008). Interviews can be used to guide grounded theory development and add context and meaning to quantitative research (Austin-Lane, Girasek, & Barbour, 2004; Patton, 2002). All interviews were conducted in English, Hindi (the main official language), or the local dialect, Chhattisgarhi, by a trained qualitative interviewer with the assistance of local interpreters.…”
Section: Methodsmentioning
confidence: 99%
“…Interviews and validation focus groups guided by the use of a semistructured guide to assure that the same concepts were explored but allowing a free flowing exploration (Corbin & Strauss, 2008). Interviews can be used to guide grounded theory development and add context and meaning to quantitative research (Austin-Lane, Girasek, & Barbour, 2004; Patton, 2002). All interviews were conducted in English, Hindi (the main official language), or the local dialect, Chhattisgarhi, by a trained qualitative interviewer with the assistance of local interpreters.…”
Section: Methodsmentioning
confidence: 99%
“…This CDC tracking system measures key state tobacco control policy outputs, including the number of states that passed preemption of stronger local ordinances with respect to youth access and clean indoor air and tobacco excise tax data from 1990 to 1999. Recent research studies indicate preemption of stronger local ordinances, which is supported by the tobacco industry, weakens effective local tobacco control policies that decrease health risks (Austin‐Lane, Girasek, & Barbour, 2004; Derthick, 2005; Givel & Glantz, 2001a; Givel & Glantz, 2004–05; Morley et al., 2002; Studlar, 2002). In addition, over 100 peer‐reviewed studies on state tobacco tax policymaking have indicated that a 10 percent rise in tobacco prices results in a decrease of between 2.5 percent to 5.0 percent in tobacco consumption (Chaloupka, Cummings, Morley et al., 2002).…”
Section: Data Sourcesmentioning
confidence: 99%
“…Interviews and validation focus groups guided by the use of a semistructured guide to assure that the same concepts were explored but allowing a free flowing exploration (Corbin & Strauss, 2008). Interviews can be used to guide grounded theory development and add context and meaning to quantitative research (Austin-Lane, Girasek, & Barbour, 2004;Patton, 2002). All interviews were conducted in English, Hindi (the main official language), or the local dialect, Chhattisgarhi, by a trained qualitative interviewer with the assistance of local interpreters.…”
Section: Interviewsmentioning
confidence: 99%